The American Illness - F.H. BUCKLEY (Yale University Press, 2013)
Fifty years ago we thought we knew how to make a country rich: selfgovernment, good education, free markets, and loads of World Bank infrastructure grants. Nothing very complicated, in short. We know better now. The gap between rich and poor countries, which we expected to shrink, has grown larger. What we failed to recognize was the role of intangible assets: the cultural values of thrift and industry, honesty in government, and the rule of law. What the rule of law might mean is, as we shall see, not always clear. But however one might defi ne it, rich countries enjoy a robust rule of law, and departures from it in third- world countries have left their citizens impoverished. More recently, America itself has suffered from an economic decline, and this book asks, with the assistance of leading scholars in the legal academy, whether a decline in the rule of law has contributed to this. America sends experts to lecture people in other countries about the importance of the rule of law, but in doing so, do we fail to recognize the beam in our own eye? Americaâ€™s legal system, and its reliance upon lawyers, has long made it the worldâ€™s outlier. Other countries seem to depend more on informal social norms and less on legal ones. Here, however, the rule of lawyers seems almost to be coded in the countryâ€™s DNA. Or so at least Edmund Burke thought, as he surveyed the men whom today we call the Found ers of America. In his 1775 Speech on the Conciliation with the Colonies, Burke attributed the â€œuntractableâ€ spirit of the colonists to their lawyers and students of law: â€œThis study renders men acute, inquisitive, dexterous, prompt in attack, ready in defence, full of resources. In other countries, the people, more simple, and of a less mercurial class, judge of an ill principle in government only by an actual grievance; here they anticipate the evil. . . . They augur misgovernance at a distance; and sniff the approach of tyranny in every tainted breeze.